A case study of integrating principles of photography and photorealistic for 3D rendering - Joon, Jong Sze; Chan, Yuen May; Weng, Khong Chee (2007)
This paper discusses the hybrid technique of merging both principles of photography and photorealistic 3D rendering approach to create a harmony between the two elements. In order to optimize the performance of 3D rendering and provide a creative solution for effective rendering method, an experiment was conducted Based on analysis of 3D rendering works, qualitative approach is selected and case study was conducted by comparing works through observation. The findings indicate the obvious difference in the understanding of basic design fundamentals accustomed in photography. The second phase of the research is targeted towards the students' maturity in understanding the content of photorealistic 3D in terms of model properties, textures, lighting and rendering. The outcome of the research serves as a guideline to understand the basic foil, of efficient photorealistic 3D rendering process for beginners with enhanced method.